CAM/TMA-DPH as a promising alternative to SYTO9/PI for cell viability assessment in bacterial biofilms - Tchatchiashvili, Tinatini; Jundzill, Mateusz; Marquet, Mike; Mirza, Kamran A.; Pletz, Mathias W.; Makarewicz, Oliwia; Thieme, Lara (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionAccurately assessing biofilm viability is essential for evaluating both biofilm formation and the efficacy of antibacterial treatments. Traditional SYTO9 and propidium iodide (PI) live/dead staining in biofilm viability assays often ace challenges due to non-specific staining, limiting precise differentiation between live and dead cells. To address this limitation, we investigated an alternative staining method employing calcein acetoxymethyl (CAM) to detect viable cells based on esterase activity, and 1-(4-trimethylammoniumphenyl)-6-phenyl-1,3,5-hexatriene p-toluenesulfonate (TMA-DPH) to assess the remaining biofilm population.MethodsBiofilms of Pseudomonas aeruginosa, Klebsiella pneumoniae, Staphylococcus aureus, and Enterococcus faecium were matured and exposed to varying concentrations of antibiotics or sterile medium. Biofilm viability was assessed using CAM/TMA-DPH or SYTO9/PIstaining, followed by analysis with confocal laser scanning microscopy (CLSM) and ImageJ-based biofilm surface coverage quantification. Viability findings were compared with colony-forming units (CFU/mL), a standard microbial viability measure.ResultsCAM/TMA-DPH staining demonstrated strong positive correlations with CFU counts across all bacterial species (r = 0.59 - 0.91), accurately reflecting biofilm vitality. In contrast, SYTO9/PI staining consistently underestimated the viability of untreated biofilms, particularly in Klebsiella pneumoniae, where a negative correlation with CFU/mL was observed (r = –0.04). Positive correlations for SYTO9/PI staining were noted in other species (r = 0.65 - 0.79). These findings underscore the limitations of membrane integrity-based staining methods and highlight the advantages of metabolic-based probes like CAM/TMA-DPH.DiscussionOur findings suggest that CAM/TMA-DPH staining provides a promising alternative to SYTO9/PI for cell viability assessment in bacterial biofilms, highlighting the advantages of metabolic-based probes over traditional membrane integrity assays. The consistency of CAM/TMA-DPH staining across different bacterial species underscores its potential to advance studies on biofilm and contribute to the development of more effective anti-biofilm treatments, which is essential for clinical management of biofilm-associated infections.